2022
DOI: 10.5194/bg-2022-167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using atmospheric observations to quantify annual biogenic carbon dioxide fluxes on the Alaska North Slope

Abstract: Abstract. The continued warming of the Arctic could release vast stores of carbon into the atmosphere from high-latitude ecosystems, especially from thawing permafrost. Increasing uptake of carbon dioxide (CO2) by vegetation during longer growing seasons may partially offset such release of carbon. However, evidence of significant net annual release of carbon from site-level observations and model simulations across tundra ecosystems has been inconclusive. To address this knowledge gap, we combined top-down ob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Based on our comparisons with the EC tower records, TCFM‐Arctic may be missing up to 78% (CO 2 ) and 40% (CH 4 ) of the episodic emissions from tundra environments during the shoulder seasons, which is considerable especially since field studies in northern Alaska (Arndt et al, 2020; Raz‐Yaseef et al, 2017) have found, at some locations, the amount of built‐up CO 2 released from soil during the spring snowmelt period can offset up to 41%–46% of summer CO 2 uptake. Additionally, regional studies (Byrne, Liu, et al, 2022; Commane et al, 2017; Schiferl et al, 2022) have documented a shift toward more respiration in autumn, that might increasingly offset summer GPP. This emphasizes the need for models to effectively account for the mechanisms driving shoulder season emissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our comparisons with the EC tower records, TCFM‐Arctic may be missing up to 78% (CO 2 ) and 40% (CH 4 ) of the episodic emissions from tundra environments during the shoulder seasons, which is considerable especially since field studies in northern Alaska (Arndt et al, 2020; Raz‐Yaseef et al, 2017) have found, at some locations, the amount of built‐up CO 2 released from soil during the spring snowmelt period can offset up to 41%–46% of summer CO 2 uptake. Additionally, regional studies (Byrne, Liu, et al, 2022; Commane et al, 2017; Schiferl et al, 2022) have documented a shift toward more respiration in autumn, that might increasingly offset summer GPP. This emphasizes the need for models to effectively account for the mechanisms driving shoulder season emissions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the boreal zone, a majority of the models evaluated here (including TCFM-Arctic) indicated the tundra domain as being, on average, neutral or a small source for NEE. However, adjusting the TCFM-Arctic tundra NEE budget to account for a potentially large underestimation of episodic CO 2 emissions during spring and autumn shoulder seasons (Arndt et al, 2020;Byrne, Baker, et al, 2022;Byrne, Liu, et al, 2022;Commane et al, 2017;Liu et al, 2022;Schiferl et al, 2022) and source (when soils are warm and less wet) (e.g., Euskirchen et al, 2014;Laine et al, 2019;Olefeldt et al, 2017;Rinne et al, 2020;Schulze et al, 1999) depending on water table depth and soil wetness.…”
Section: Regional Necb Emission Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study did not consider temporal changes in SOC properties. However, out study period was relatively short, during which limited SOC changes are expected to occur in the undisturbed tundra [55]. On the other hand, we assembled three different in-situ SOC datasets, and the associated differences in the soil sampling process may add large uncertainties to the assembled surface (0-10 cm) SOC dataset.…”
Section: B Regional Soc Mappingmentioning
confidence: 99%